2020
DOI: 10.1021/acs.langmuir.0c02402
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Dandelion-like p–p Type Heterostructure of Ag2O@CoO for Bifunctional Photoelectrocatalytic Performance

Abstract: A novel three-dimensional purple dandelion-like hierarchical Ag2O@CoO heterojunction with an appropriate redox potential was constructed by chemical precipitation of Ag2O nanoparticle on flower-like CoO. By feat of this hierarchical structure, the Ag2O@CoO photocathode showed significantly high photoelectroreduction activities toward p-nitrophenol (p-NP) and Cr­(VI). The high performance of Ag2O@CoO was mainly attributed to the specific structural characteristics and synergistic effect of each chemical compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 62 publications
1
6
0
Order By: Relevance
“…In addition, the obtained charge carrier densities of g-C 3 N 4 , BiOF, and 6% g-C 3 N 4 /BiOF are 1.93, 2.12, and 2.56 × 10 23 , respectively. The alleviated charge carrier density of 6% g-C 3 N 4 /BiOF portrays that the heterojunction of g-C 3 N 4 and BiOF endorses the charge carrier migration . To examine the charge-transfer ability of the electrode materials at the electrode/electrolyte interface in 0.5 M NaOH, electrochemical impedance spectroscopy (EIS) was performed under dark, front, and back light illumination conditions (Figure A–C).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…In addition, the obtained charge carrier densities of g-C 3 N 4 , BiOF, and 6% g-C 3 N 4 /BiOF are 1.93, 2.12, and 2.56 × 10 23 , respectively. The alleviated charge carrier density of 6% g-C 3 N 4 /BiOF portrays that the heterojunction of g-C 3 N 4 and BiOF endorses the charge carrier migration . To examine the charge-transfer ability of the electrode materials at the electrode/electrolyte interface in 0.5 M NaOH, electrochemical impedance spectroscopy (EIS) was performed under dark, front, and back light illumination conditions (Figure A–C).…”
Section: Resultssupporting
confidence: 82%
“…The alleviated charge carrier density of 6% g-C 3 N 4 /BiOF portrays that the heterojunction of g-C 3 N 4 and BiOF endorses the charge carrier migration. 54 To examine the charge-transfer ability of the electrode materials at the electrode/electrolyte interface in 0.5 M NaOH, electrochemical impedance spectroscopy (EIS) was performed under dark, front, and back light illumination conditions (Figure 8A−C). The Nyquist plot of 6% g-C 3 N 4 / BiOF displays a lower resistance of charge transfer (R ct ), 10.27 kΩ, compared to g-C 3 N 4 (15.23 kΩ) and BiOF (12.85 kΩ) under front light illumination.…”
Section: Photoelectrochemicalmentioning
confidence: 93%
“…Taking RhB as a model pollutant, we found that in the presence of 1 sun illumination (100 mW/cm 2 ), SODSNs can remove ∼97% RhB from the solution in just 180 s, and within 300 s, the amount of RhB goes below 1%. These numbers are very promising compared to other reports of Ag 2 O nanoparticles alone or any hybrid structures of Ag 2 O. ,,,,, These nanoparticles can easily be coated onto various substrates like glass, silicon, cotton cloth, sponge, and tissue paper. The flexibility of coating and multifunctional properties of these SODSNs make them a promising candidate for versatile applications.…”
Section: Introductionmentioning
confidence: 87%
“…16 The rate of electron (e − ) and hole (h + ) recombination is decreased by using an appropriate external bias voltage, which effectively improves the efficiency of PEC. 17 The advantages of the photoelectrocatalytic technique are the use of solar energy, low cost, and environmental protection. 18 Under light conditions, semiconductors generate e − from the valence band (VB) to the conduction band (CB).…”
Section: ■ Introductionmentioning
confidence: 99%